Evaluation of the degradation properties of carbonate substituted hydroxyapatite-poly(ε-caprolactone) composites - Ege,D; Lee,K; Bismarck,A; Best,S; Cameron,R (Key Engineering Materials, 2012)
The aim of this work is to produce and characterise carbonate substituted hydroxyapatite (CHA) reinforced polycaprolactone (PCL) nanocomposites with a controlled degradation rate in order to match the rate of bone in-growth. The ideal degradation time for this purpose is estimated to be around 5-6 months however, in vivo, PCL degrades over a period of 2 to 3 years. It has been reported that NaOH surface treatment can accelerate the degradation of PCL [1-3]. In order to further modify the degradation rate of PCL, the effects of the incorporation of different volume fractions of CHA in samples surface treated with NaOH was investigated. CHA was produced by wet chemical synthesis. Samples comprising 8, 19, 25 wt% uncalcined CHA-PCL composites were produced by twin screw extrusion which were then injection moulded into cylinders. In order to accelerate the degradation rate of PCL, it was surface treated with 5 M NaOH for 3 days prior to PBS studies. The degradation profile was examined by % weight loss and % water uptake measurements. NaOH treatment was observed to erode the polymer surface and the polymer-filler interface. On subsequently degrading the pre-treated samples in PBS, it was observed that with increasing fraction of CHA, the degradation rate in PBS of the sample increased. Up to 8 wt % CHA filler there appeared to be little change in the degradation properties of the NaOH treated samples with the onset occurring after 60 days. However there was a marked acceleration of degradation for samples containing 19 wt% when degradation appeared to occur immediately. In conclusion, the addition of CHA significantly affects the behaviour of PCL. © (2012) Trans Tech Publications.